Using online social networks among university students in Mexico Towards the construction of a state of knowledge (2004-2014). - Domínguez Pozos, Fernando de Jesús (2022)
The present article constitutes a review of studies about the use that undergraduate students give to social network in Mexico. The objective is to draw an overview that allows us to know how these studies are developed. Our purpose is to identify the results reached at the moment as well as to point out different approaches, relevant contributions and themes tackled during the last years. Through this paper we can observe different lines of investigation for future research that allow us to know better undergraduate students.